'Who's who' in renal sphaerosporids (Bivalvulida: Myxozoa) from common carp, Prussian carp and goldfish--molecular identification of cryptic species, blood stages and new members of Sphaerospora sensu stricto - Holzer, Astrid Sibylle; Bartošová, P; Pecková, H; Tyml, T; Atkinson, S; Bartholomew, J; Sipos, D; Eszterbauer, E; Dyková, I (Parasitology, 2013)
Myxozoans are a group of diverse, spore-forming metazoan microparasites bound to aquatic environments. Sphaerospora dykovae (previously S. renicola) causes renal sphaerosporosis and acute swim bladder inflammation (SBI) in juvenile Cyprinus carpio carpio, in central Europe. A morphologically similar species with comparably low pathogenicity, S. angulata has been described from C. c. carpio, Carassius auratus auratus and Carassius gibelio. To clarify uncertainties and ambiguities in taxon identification in these hosts we decided to re-investigate differences in spore morphology using a statistical approach, in combination with SSU and LSU rDNA sequence analyses. We found that developing spores of S. angulata and S. dykovae cannot be distinguished morphologically and designed a duplex PCR assay for the cryptic species that demonstrated S. dykovae is specific to C. c. carpio, whereas S. angulata infects C. a. auratus and C. gibelio. The molecular identification of myxozoan blood stages in common carp and goldfish, which had previously been ascribed to Sphaerospora spp. showed that approximately 75% of blood stages were from non-sphaerosporid coelozoic species infecting these cyprinids and more than 10% were from an alien species, Myxobilatus gasterostei, developing in sticklebacks. We hereby report non-selective myxozoan host invasion and multi-species infections, whose role in SBI still requires clarification.
Keywords: druhová specificita; polymerázová řetězová reakce; Fish Diseases; genetická variace; fylogeneze; Phylogeny; ribozomální DNA; Europe; molekulární sekvence - údaje; prevalence; Kidney; kapři; Myxozoa; Species Specificity; Evropa; Blood; Animals; parazitární nemoci u zvířat; ledviny; zvířata; nemoci ryb; Parasitic Diseases, Animal; Carps; Prevalence; Molecular Sequence Data; Polymerase Chain Reaction; krev; DNA, Ribosomal; Genetic Variation